The Effect of Comic Strip as Instructional Method in Enhancing Students’ Writing Skills - Amrizal Amrizal (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2022)
There have been several studies on the use of comics as an instructional tool for reading, but less on their use to writing, particularly descriptive text. The goal of this study is to find out how the comic strip affects the writing skills of students in the Islamic education program STAIN Mandailing Natal, especially their descriptive writing skills . This study was a experiment method. It was done by two classes, one called the experimental class and the other called the control class. Each class had 35 students. The Random sampling is used in the sampling of this study. This study uses SPSS windows 10 or statistical analysis to construct the T-Test while analyzing the data. This research finds that comic strips may improve students' descriptive writing. Through comic strips, students enhanced their writing abilities in all areas. The learning process is more efficient because of the use of simple language, clear images, and follow-up questions to ensure that everyone understood what was going on.